Community Service Training on Material Flow Cost Accounting (MFCA) for Micro, Small, and Medium Enterprise (MSME) Entrepreneurs - Anis, Idrianita; Herawati, Vinola; Faizal, Amir; Afiyah, Yayah Sholehatul; Avrillia, Vera (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2023)
In the last two decades, concern for environmental issues has become a regulatory concern at the international and national levels. Many methods have been developed to reduce negative impacts on business activities, including Material Flow Cost Accounting (MFCA) technology that shows an increasing trend among companies and Micro, Small, and Medium Enterprises (MSMEs) in developing countries. The benefit of MFCA technology is its superiority in identifying material losses (harmful products) during production. At the same time, this is known at the end of the process in the conventional accounting system. Then by implementing MFCA technology, business people can take initiatives to reduce material losses and achieves resource efficiency. In addition to efforts to reduce material losses, MFCA technology will encourage business-enhancing practices by reducing costs, reducing carbon emissions, and increasing operational efficiency. This Community Service Program aims to provide training on sustainable business principles by applying MFCA technology for MSME Entrepreneurs at Bina Amanah School of Entrepreneur Cordova in South Tangerang, Banten Province. Using the action research method increases participants' knowledge after the MFCA training.